Nocturnal fish chorusing activity in the central Red Sea mesophotic reef zone and adjacent shallow sites - Havlik, Michelle-Nicole; Parry, Anieka J.; Steckbauer, Alexandra; Watts, Marta Ezeta; Marchese, Fabio; Benzoni, Francesca; Duarte, Carlos M. (Frontiers in Remote Sensing, 2025)
Through sharing characteristics of chorus activity, especially in regions that are particularly data deficient, we can aim at a broader, global understanding of fish chorusing and consequently important spatiotemporal changes in habitat use by schooling fish. Here, we identify seasonal changes in fish chorusing activity using passive acoustic monitoring, in the central Red Sea mesophotic and adjacent shallow coral reef zones. For this study, recorders were placed in the mesophotic coral reef zone (70–80 m), and adjacent shallow reef sites (10 m), over 2 weeks during summer and winter seasons. A total of eleven choruses were identified and catalogued according to timing, location and acoustic characteristics of frequency and sound pressure levels. The presence of choruses in both deep and shallow reef sites is indicative of critical habitat for fish foraging, courtship, spawning, and/or migratory activity. All but two choruses were found to originate at or near the mesophotic sites. Four choruses unique to summer and winter (n=3 and 1 respectively) were most prevalent in soundscapes. Temperature and oxygen levels, measured to document conditions under which the choruses were present, showed little change across the mesophotic zone even between seasons, while daily fluctuation occurred in the adjacent shallow sites in both seasons.